Logan Medallist 7. Appinite Complexes, Granitoid Batholiths and Crustal Growth: A Conceptual Model - Murphy, J. Brendan; Collins, William J.; Archibald, Donnelly B. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2022)
Appinite bodies are a suite of plutonic rocks, ranging from ultramafic to felsic in composition, that are characterized by idiomorphic hornblende as the dominant mafic mineral in all lithologies and by spectacularly diverse textures, including planar and linear magmatic fabrics, mafic pegmatites and widespread evidence of mingling between coeval mafic and felsic compositions. These features suggest crystallization from anomalously water-rich magma which, according to limited isotopic studies, has both mantle and meteoric components. Appinite bodies typically occur as small (~2 km diameter) complexes emplaced along the periphery of granitoid plutons and commonly adjacent to major deep crustal faults, which they preferentially exploit during their ascent. Several studies emphasize the relationship between intrusion of appinite, granitoid plutonism and termination of subduction. However, recent geochronological data suggest a more long-lived genetic relationship between appinite and granitoid magma generation and subduction.Appinite may represent aliquots of hydrous basaltic magma derived from variably fractionated mafic underplates that were originally emplaced during protracted subduction adjacent to the Moho, triggering generation of voluminous granitoid magma by partial melting in the overlying MASH zone. Hydrous mafic magma from this underplate may have ascended, accumulated, and differentiated at mid-to-upper crustal levels (ca. 3–6 kbar, 15 km depth) and crystallized under water-saturated conditions. The granitoid magma was emplaced in pulses when transient stresses activated favourably oriented structures which became conduits for magma transport. The ascent of late mafic magma, however, is impeded by the rheological barriers created by the structurally overlying granitoid magma bodies. Magma that forms appinite complexes evaded those rheological barriers because it preferentially exploited the deep crustal faults that bounded the plutonic system. In this scenario, appinite complexes may be a direct connection to the mafic underplate and so its most mafic components may provide insights into processes that generate granitoid batholiths and, more generally, into crustal growth in arc systems.